DEGRADATION KINETICS OF POLYVINYL CHLORIDE STABILIZED WITH PALMITIC ACID-METALLIC MIXTURES - Newman Nainggolan, Stevanus
Polyvinyl chloride (PVC) is a polymer with wide applications in industries because of its physical and chemical properties. PVC is the third most used polymer in the world after polyethylene (PE) and polypropylene (PP). The disadvantage of using PVC is that dehydrochlorination may happen at low temperatures, which may lead to the material being brittle and hard to mold. Hence, thermal stabilizers need to be added to PVC resin to avoid thermal degradation.